2017
DOI: 10.1002/slct.201701148
|View full text |Cite
|
Sign up to set email alerts
|

A Metalloporphyrin-Peptide Conjugate as an Effective Inhibitor of Amyloid-β Peptide Fibrillation and Cytotoxicity

Abstract: Molecules that inhibit Aβ misfolding have received considerable attention in view of their potential use in the prevention or treatment of Alzheimer's disease. We designed a peptide‐porphyrin conjugate incorporating two recognition sites enabling it to interact strongly with the Aβ42 peptide. The inhibitory effect on Aβ42 fibril formation was determined in aqueous solution by a variety of spectroscopic techniques including UV‐vis, fluorescence, Circular Dichroism, Dynamic Light Scattering, Maldi‐Time of Flight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…We found that THPP and bCD weren ot able to prevent oligomert oxicity. The His residues may coordinate zinc(II) of ZnCDTHPP,f urtherc ontributingt oh amper the peptideh ydrolysis close by.T he interaction between az inc-coordinated porphyrin conjugate and the histidine residues of the Ab 42 N-terminus has been previously evoked, [11] thus supporting the mechanism we hypothesized.Overall, the proteomic analysiso ft he Ab 42 fragments reveals that CDTHPP and ZnCDTHPP interact with aw ide sequence region of Ab 42 ,e ncompassing an LVFF motif, which is involved in the self-recognition mechanism of the amyloid aggregation and is common to most AD b-sheetb reaker peptides. These datac onfirm that CDTHPP and ZnCDTHPP show an europrotective activity arising from the synergyo ft he THPP and bCD properties and possess unique anti-oligomeric activity not found in the parentc ompounds.S uch resultss uggest that CDTHPP conjugatesi nterfere with Ab 42 ,blockingi ts cytotoxicity.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…We found that THPP and bCD weren ot able to prevent oligomert oxicity. The His residues may coordinate zinc(II) of ZnCDTHPP,f urtherc ontributingt oh amper the peptideh ydrolysis close by.T he interaction between az inc-coordinated porphyrin conjugate and the histidine residues of the Ab 42 N-terminus has been previously evoked, [11] thus supporting the mechanism we hypothesized.Overall, the proteomic analysiso ft he Ab 42 fragments reveals that CDTHPP and ZnCDTHPP interact with aw ide sequence region of Ab 42 ,e ncompassing an LVFF motif, which is involved in the self-recognition mechanism of the amyloid aggregation and is common to most AD b-sheetb reaker peptides. These datac onfirm that CDTHPP and ZnCDTHPP show an europrotective activity arising from the synergyo ft he THPP and bCD properties and possess unique anti-oligomeric activity not found in the parentc ompounds.S uch resultss uggest that CDTHPP conjugatesi nterfere with Ab 42 ,blockingi ts cytotoxicity.…”
supporting
confidence: 82%
“…In this work, the biological properties of 5[4-(6-O-b-cyclodextrin)-phenyl],10,15,20-tri(4-hydroxyphenyl)-porphyrina nd its zinc complex were tested, as new molecules that interactw ith Ab and effectively preventi ts cytotoxicity.W ef ound that these systems can cross the cell membrane to deliver Ab intracellularlya nd promote its clearance. [10,11] Moreover,n umerous studies have also shown that sugars such as trehalose (Tre) and cyclodextrins (CDs)m ay be protectivea gainst neuronal degeneration observed in AD. Much efforth as therefore been made to investigate the compositiono fa myloid plaques, the mechanism underlying Ab fibril formation,a nd the parameters that could contribute to the Ab toxicity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro, the toxic effect of amyloid β peptides on neuron‐like cells (PC12) was greatly inhibited by the conjugate in a dose dependent manner, without effect on the cell viability. A possible mechanism of inhibition of amyloid β peptides formation by a zinc–porphyrin–KLVFF conjugate has been recently proposed, consisting in the generation of off‐pathway aggregated forms of amyloid β peptides not evolving into oligomeric or proto‐fibrillary toxic forms …”
Section: Biomarkers Detection and Emerging Therapiesmentioning
confidence: 99%